The effect of gelagah stem extract on blood glucose levels in male white rats induced with alloxan - Simatupang, Veronica Triwindari; Lubis, Asyrun Alkhairi; Nasution, Ali Napiah; Lumbantobing, Christina JRE; Fioni, Fioni; Rahimi, Armon (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2024)
Diabetes mellitus is a metabolic disorder characterized by elevated blood glucose levels due to insulin deficiency, insulin resistance, or both. This study aimed to investigate the effects of gelagah stem extract (Saccharum spontaneum L.) on blood glucose levels in male Sprague-Dawley rats induced with alloxan. Experimental rats were divided into six groups: a normal control group, a negative control group (administered 100 mg/kg body weight alloxan), a positive control group (administered 5 mg/kg body weight glibenclamide), and three treatment groups administered gelagah stem extract at doses of 100, 200, and 400 mg/kg body weight. Results showed that all doses of gelagah stem extract significantly reduced blood glucose levels in alloxan-induced diabetic rats. Statistical analysis (Post hoc LSD) confirmed that the decrease in blood glucose levels was significantly different between the treatment groups and the negative control group (p < 0.05).